Literatur Review: Strategi Intervensi Psikologi pada Korban Kekerasan Seksual DIitinjau dari Teori Ekologi Brofenbrenner - Ney, Wulandari (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2024)
The phenomenon of sexual violence currently does not show a significant decline, apart from that the psychological impact it causes is not simple. The aim of this study was to identify the most effective approaches in helping victims of sexual violence recover. In this study, the method used by researchers is a literature review study with a narrative approach (Narrative Review). This method aims to allow wider exploration of the topic and be more flexible. The results of the study found that the psychological intervention strategy based on Brofenbrener's ecological theory is to pay attention to several important things, namely the importance of interventions that focus on trauma recovery and increasing self-acceptance of victims, the importance of involving family members and friends in the victim's therapy process, so the need for education of family and friends. is very necessary, as well as a comprehensive government policy in handling and preventing cases of sexual violence which can start from the allocation of adequate resources for psychological services as well as legal reform in considering the psychological impact of victims. By analyzing these factors, psychological intervention strategies for victims of sexual violence can be achieved. to the maximum.